سروشت و پێگەی دیفاكتۆی باكوری سوریا (ڕۆژئاڤای كوردستان) لە هاوكێشە هەرێمایەتییەكاندا – دەرفەت و ئالینگاریەكان - شوکری, د. نەوزاد عبدللە; عبدللە, بەناز ڕەفیق (Sulaimani Journal for Humanities, 2023)
This article attempts to expalin the position of Kurdish de facto state in Syria in the political equation in the region. In this regarad, the article would endeavor to analyse the impact of the internal and reginal factors on the future of Kurdish automonus region. Moroover, the article attempts to exmine challenges and threats which face the kurds in Syria. For clarifying arguemts, this article will use the concept of de facto state and descterptive theory. It can be said that emergence of Kurdish region in Syria dates back to time of the eruption of Arab spring and in particular the uprising in Syria in 2011. Following eruption of demonsration in Syria, intensifying the secerian conflict and then intervention of regional actors in Syrian conflit the kurds took the opportunity to control all their territory for first time since establishment of the Syrian state Further, emergence of ISIS in Syria and Iraq and then formation of international coalation to confront this terrorist group further enhanced Kurdish position in Syria. In particular, the US started to support the kurds militarily to confrot ISIS in Syria. This is because the Kurdish armed gouprs have been the only US trusted partner in Syria. Having said that and despite the opprtunitty that kurds have, there is a lot of internal and regional threat that faces the Kurdish autonums region in Syria